Freeze-thaw stability of enzyme-treated pandesal - Castillo, Czarina C.; Azanza, Ma. Patricia V. (2009.)
ABSTRACT The study evaluated the stability of enzyme-treated pandesal subjected to five freeze-thaw cycles. The most acceptable base pandesal formulation was chosen from three published recipes through a multilevel sensory evaluation (n=35). The chosen pandesal formulation after three levels of sensory evaluation was the modified Fojas-Luna (2005) utilizing instant active yeast and straight-dough method. It had the following sensory attributes: a slightly strong odor; light brown crust with intermediate thickness and hardness; slightly creamy-white crumb with fine mouthfeel; intermediate moistness and chewiness; moderately weak sourness; and intermediate sweetness and flavor. Enzymatic modification was performed through the application of maltogenic α-amylase at 0.001% and 0.01%, and pentosanase at 0.002% and 0.012% based on flour weight. Physico-chemical tests, and sensory evaluation (n=35) showed that enzyme treatments resulted to an improvement of acceptability ratings in pandesal relative to the control. The 0.002% pentosanase-treated pandesal was chosen since it was perceived as significantly (p<0.05) more tender, soft, and moist. Control and enzyme-treated pandesal were subjected to five consecutive freezing (-18°C, 48 h) and thawing (12°C, 24 h) cycles. The pentosanase-treated pandesal remained more acceptable than the control at the end of five freeze-thaw cycles based on the results of sensory evaluation, and physico-chemical and microbiological tests performed. Both control and pentosanase-treated pandesal retained acceptable quality even after five freeze-thaw cycles. This may indicate that pandesal could be subjected to five freeze-thaw cycles without significantly affecting the sensory acceptability of pandesal. Studies may be performed to establish the mechanisms of pentosanase in delaying bread staling, and the benefits of combining enzyme treatment and freezing in preserving the quality and freshness of pandesal and other baked products.
Thesis (B.S. Food Technology)--University of the Philippines Diliman
Keywords: Bread -- Preservation